Strategic management of relations of public universities with enterprises in Poland - Ławicka, Magdalena (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The purpose of the research was to characterize relations between universities and enterprises. In this study, as the subject of consideration and research, the economic faculties of public universities in the West Pomeranian Voivodeship were selected. The following research methods were used: critical analysis of the literature and diagnostic questionnaire method. The article presents a proposal of strategic relationship management of universities.